Guidelines for essential trauma care (World Health Organization, 2004)
Injury has become a major cause of death and disability worldwide. Organized approaches to its prevention and treatment are needed. These guidelines seek to set achievable standards for trauma treatment services which could realistically be made available to almost every injured person in the world. They then seek to define the resources that would be necessary to assure such care. The authors have developed a series of resource tables for essential trauma care that detail the human and physical resources that should be in place to assure optimal care of the injured patient at the range of health facilities throughout the world, from rural health posts, to small hospitals, to hospitals staffed by specialists, to tertiary care centres. They also take into account the varying resource availability across the spectrum of low- and middle-income countries. Finally, a series of recommendations is made on methods to promote such standards including training, performance improvement, trauma team organization and hospital inspection